Preoperative Hyponatremia Indicates Complicated Acute Appendicitis. (31st March 2022) - Symeonidis, Nikolaos G.; Pavlidis, Efstathios T.; Psarras, Kyriakos K.; Stavrati, Kalliopi; Nikolaidou, Christina; Marneri, Alexandra; Geropoulos, Georgios; Meitanidou, Maria; Andreou, Emili; Pavlidis, Theodoros E.
Abstract : Introduction . Acute appendicitis is the most common surgical emergency. Early detection of patients with complicated appendicitis leads to prompt surgical management and better outcome. This study investigated the relationship between the severity of acute appendicitis and the presence of preoperative hyponatremia. Materials and Methods . We retrospectively reviewed the medical files of adult patients operated on for acute appendicitis over a 6-year period. Hyponatremia was defined as serum sodium level of ≤135 mEq/L. Patients were classified into complicated appendicitis and noncomplicated appendicitis according to operative findings and/or histopathology reports. Results . A total of 129 patients were identified and included in this study. Complicated appendicitis was found more frequently in female patients and older patients. Hyponatremia was found significantly more frequently in patients with complicated appendicitis (p < 0.001 ) and also in patients with perforation than without perforation (p = 0.047 ). Conclusions . The present study demonstrated that preoperative hyponatremia is associated with complicated appendicitis. Serum sodium levels, a routine, low-cost laboratory test, could act as an accessory marker aiding surgeons in earlier identification of gangrenous or perforated acute appendicitis.